Animating black and brown liberation : a theory of American literatures - Datcher, Michael, 1967- (State University of New York Press, 2019)
"Animating Black and Brown Liberation introduces a vital new tool for reading American literatures. Rooted in both ancient Egyptian ideas about life and cutting-edge theories of animacy, or levels of aliveness, this tool--ankhing--enables Datcher to examine the ways African American and Latinx literatures respond to and ultimately work to resist hegemonic forces of neoliberalism and state-sponsored oppression. Weaving together close readings and politically informed philosophical reflection, Datcher considers the work of writer-activists such as Toni Cade Bambara, Cherríe Moraga, Gloria Anzaldúa, June Jordan, Salvador Perez, and Ishmael Reed, in light of theoretical interventions by Jane Bennett, Mel Y. Chen, Bruno Latour, Michel Foucault, Paulo Freire, and Erica R. Edwards. How, he asks, can cultural production positively influence Black and Brown material conditions and mobilize collective action "off the page"? How can art-based counterpublics provide a foundation for Black and Brown community organizing? What emerges finally from Datcher's innovative analysis is a much-needed account of the links between embodied experiences of racialization, as well as a fresh vision of twentieth and twenty-first century American literature as a repository of emancipatory strategies with real-world applications"--